Pelaksanaan Hubungan Kerja Antara Rumah Sakit Dengan BPJS Kesehatan Dalam Program Jaminan Kesehatan Nasional - HASANAH, NIDA AMALIA; , Inayah, S.H, M.H (2017)
The purpose of this study was to know implementation of cooperation agreement between hospital with BPJS Health, obstacle hospital and BPJS Health also BPJS Health effort to tackle the obstacles of program JKN. This is an emperical legal research. It was conducted at Mulia Hati Hospital in Wonogiri, Islamic Hospital in Klaten and BPJS Health branch Boyolali. It uses primary data as the data source with qualitative analysis technique. The results showed that: the implementation of cooperation agreement showing opened characteristic in law of agreement. The obstacles in JKN program: (1) regulations dynamic and retroactive; (2) health service by the system referral not going well; (3) the lack of awareness hospitals and participants in order to understand the regulation of JKN. BPJS Health effort: (1) hospital submit an objection to regulator about regulation's problem; (2) BPJS Health prepared a room called education room for participants.